Consequences of Stinging Plankton Blooms on Finfish Mariculture in the Mediterranean Sea - Bosch-Belmar, Mar; Milisenda, Giacomo; Girons, Albert; Taurisano, Valentina; Accoroni, Stefano; Totti, Cecilia; Piraino, Stefano; Fuentes, Verónica (Frontiers in Marine Science, 2017)
In recent years, caged finfish mariculture across European seas suffered production losses by severe fish mortality, following episodic outbreaks of invertebrate cnidarian stingers. Due to their stinging cells and injectable venoms, medusozoan jellyfish or drifting propagules of polyp colonies at high density may impair caged fish health through toxic effects on vulnerable tissues of gills and skin, and related secondary bacterial infections. Gill disorders in European sea bass (Dicentrarchus labrax) fish farms along the Spanish Mediterranean coast are commonly reported, but regular monitoring of the frequency of cnidarian outbreaks and their potential impacts on caged fish is still poorly enforced. In this study, two sea bass mariculture farms in Southern Spain (Málaga; Almería) were monitored biweekly for zooplankton, phytoplankton and fish gills condition, over 13 or 30 months for the Málaga and Almería facilities respectively, within the period 2012 – 2014. Significant, direct correlations were found among low water temperature, recorded fish mortalities, and high abundances of planktonic cnidarians, particularly of the hydrozoan siphonophores Muggiaea atlantica and M. kochii, and the larval stage of Ectopleura larynx, a common member of cage biofouling communities. A significant relationship between cnidarian densities and the quantitative scoring of gill pathology was also observed. In addition, high densities of long-bristled planktonic diatoms (Chaetoceros spp.) coincided with a major fish mortality event (April 2012, Almería farm). Standardised monitoring of plankton dynamics and composition may help in promoting response capacities of Mediterranean mariculture managers to fish health challenges (such as stinging plankton blooms) by a) improving diagnostic tools and preventative countermeasures and b) supporting the development of science-based spatial planning and sustainable growth of coastal mariculture.